EFFORTS TO IMPROVE KNOWLEDGE ABOUT DENTAL CARIES AT UPT SD N 01 SOUTH YOGYAKARTA - Pramono, Isnaini Agus; Syifa , Mulyana; Saputri , Kiki; Meliana , Rahma; Azizah , Rahmalia Nurul; Tika , Rahma Maulana; Amarazika , Vina; Sari , Nur Zulita (Inspirasi: Jurnal Pengabdian Masyarakat, 2025)
Background & Objective: The problem of dental caries in school-age children is still a serious concern in Indonesia, especially in areas with limited health education such as SD N 01 South Yogyakarta. This community service activity aims to improve students’ knowledge through interactive and applicable counseling. Method: The methods used include pre-tests, counseling with animated video media and demonstrations, and post-tests. Result: The results showed a significant increase in student knowledge, with 80% of respondents in the good knowledge category after the counseling, compared to only 15% before the activity. This success reflects the effectiveness of the educational approach based on behavior and visual communication. This activity produced outputs in the form of increased knowledge, activity documentation, and scientific articles ready for publication. Follow-up plans include the formation of UKGS cadres and periodic evaluations. Conclusion: This counseling is expected to be the first step towards a culture of dental health awareness in elementary school environments.